Cerebral palsy in preterm infants - Demeši Drljan, Čila; Mikov, Aleksandra; FilipoviĆ, Karmela; TomaŠeviĆ TodoroviĆ, SneŽana; KneŽeviĆ, Aleksandar; Krasnik, Rastislava (Vojnosanitetski pregled, 2017)
Background/Aim. Cerebral palsy (CP) is one of the leading causes of neurological impairment in childhood. Preterm birth is a significant risk factor in the occurrence of CP. Clinical outcomes may include impairment of gross motor function and intellectual abilities, visual impairment and epilepsy. The aim of this study was to examine the relationships among gestational age, type of CP, functional ability and associated conditions. Methods. The sample size was 206 children with CP. The data were obtained from medical records and included gestational age at birth, clinical characteristics of CP and associated conditions. Clinical CP type was determined according to Surveillance of Cerebral Palsy in Europe (SCPE) and topographically. Gross motor function abilities were evaluated according to the Gross Motor Function Classification System (GMFCS). Results. More than half of the children with CP were born prematurely (54.4%). Statistically significant difference was noted with respect to the distribution of various clinical types of CP in relation to gestational age (p
Keywords: Cerebral palsy; risk factors; infant; premature